PERANGKAT PEMBELAJARAN IPA BERBASIS INKUIRI TERBIMBING DENGAN TUGAS PROYEK MATERI SISTEM EKSKRESI UNTUK MENUNTASKAN HASIL BELAJAR SISWA SMP - Baharuddin Baharuddin; Sifak Indana; Toeti Koestiari (Universitas Syiah Kuala, 2017)
Abstract. This research purposed to produce science learning materials that eligible to complete student learning achievement at junior high school of the System of Excretion materials. The development of this learning tool based on Dick and Carey model and the using test based One Group Pretest-Posttest Design. The test conducted in eighth grade student of SMP Negeri 16 Poleang Tengah. This research consisted of two stages: 1) Developing the learning materials consisted of lesson plan, student’s book, and student’s worksheet, and learning achievement test validated by experts. 2) Implementation of the validated learning materials which instrument that used in this research are validation sheet, observational sheet of learning accomplishment, the learning constraints, observational sheet of student’s activity, and Student’s response questionnaire. The result showed that: 1) The learning materials were valid; 2) the lesson plan accomplishment was categorized as good; 3) The student activities indicated that they learn to actively build their own knowledge through a process of inquiry; 4) The students responded positively to the learning process; 5) The student’s learning achievements of attitude, knowledge, and skill aspects were accomplished. Based on the following results can be concluded that the science learning materials based on guided inquiry with a project task on Excretion of System were valid, practical, and effective. Thus the science learning materials can be used on the learning process and proofed to be effective to complete student’s learning achievement.Keywords: Guided inquiry, project task, completeness of student’s, excretion system.